Proceedings of the 2004 ACM Symposium on Applied Computing 2004
DOI: 10.1145/967900.967950
|View full text |Cite
|
Sign up to set email alerts
|

Using semi-lagrangian formulations with automatic code generation for environmental modeling

Abstract: An import issue for numerical weather prediction modes (NWP) is the time it takes to produce a valid forecast. One factor, which greatly influences this simulation time is the size of the time step. However, time step size is often limited by the numerical stability of the used advection schemes. Available schemes include semiimplicit Eulerian and semi-Lagrangian schemes. In principal, semiLagrangian formulations result in irregular communications on parallel architectures. In this paper we describe automatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…For our implementation of the model, we let CTADEL generate scalar code which we have extended with a halo by hand [17]. This halo is communicated between the processors using MPI calls.…”
Section: Full Halo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our implementation of the model, we let CTADEL generate scalar code which we have extended with a halo by hand [17]. This halo is communicated between the processors using MPI calls.…”
Section: Full Halo Methodsmentioning
confidence: 99%
“…In previous work, [16,17], we have explained how to automatically generate code for semi-Lagrangian methods from a specification of the model using the CTADEL tool [15,18]. With a number of experiments we have shown that these generated codes can compete with hand-written code on both scalar and parallel architectures.…”
Section: Introductionmentioning
confidence: 99%